PROFIL DAN ORIENTASI KEBIJAKAN LUAR NEGERI INDONESIA PASCA ORDE BARU - Alami, Athiqah Nur (Jurnal Penelitian Politik, 2011)
Formation oftheprofile and orientation oflndonesian foreignpolicy in post New Order era is closely relatedto domesticfactors ofdemocratization and externalfactors ofglobalization Democratization movement has prompted the emergence ofnew issues and actors at the national and international level Thefocus in global interactionsand issues offoreign policy is no longer solely associated with traditional issues but also issues of economicsocial culture and religion The linkage between the issues makes the actors in foreign policy are more diverseThe process offormulating and implementing Indonesian foreign policy in post New Order era shows the trendofthe involvement ofstate actors which extends horizontally and vertically as well as non state actors Thereforeit affects the configuration and structure of Indonesian foreign policy and the pattern or style of diplomacy thatplayed by the head ofgovernment Meanwhile the dynamics ofnational economic andpolitical situation after theNew Order era is the main variables that determine Indonesia sforeign policy orientation The governments fromPresident Habibie to President Susilo Bambang Yudhoyono have put the agenda ofeconomic recovery as the maincomponent that directs Indonesianforeign policy However the orientationfaces a dilemma ifit is associated withthe implementation offree and active policy as a basic principle oflndonesian foreign policy